Determination of Shear Modulus of Erythrocyte Membranes in Suspension - Gordienko, E. A.; Todrin, A. F.; Osetsky, A. I.; Popivnenko, L. I. (Problems of Cryobiology and Cryomedicine, 2010)
A dynamic method and a device are described; an algorithm for calculation of the average shear modulus of membranes of suspended erythrocytes flowing through a flat canal is suggested. Experimental data on erythrocyte membrane shear modulus depending on temperature and terms of hypothermic storage of blood are presented.